Influence of detector motion in entanglement measurements with photons - Landulfo, Andre G. S. [UNESP]; Matsas, George Emanuel Avraam [UNESP]; Torres, Adriano C. [UNESP] (Amer Physical Soc, 2010)
We investigate how the polarization correlations of entangled photons described by wave packets are modified when measured by moving detectors. For this purpose, we analyze the Clauser-Horne-Shimony-Holt Bell inequality as a function of the apparatus velocity. Our analysis is motivated by future experiments with entangled photons designed to use satellites. This is a first step toward the implementation of quantum information protocols in a global scale.